Clinical and Epidemiological Characteristics of Kawasaki Disease - Shamsizadeh, Ahmad (Jundishapur J Microbiol, 2014)
BACKGROUND: Kawasaki disease (KD) is an acute multisystem vascular syndrome of unknown etiology that is the leading cause of acquired heart disease in children of developed counties. OBJECTIVES: We aimed to evaluate the epidemiological characteristics and clinical manifestations of KD in children residing in the southwest of Iran. PATIENTS AND METHODS: In this retrospective study, we reviewed the medical records of all children with KD who had been admitted to the main children’s hospital of Ahvaz, southwest Iran, from March 2000 to March 2010. Data regarding clinical and epidemiological characteristics, management, and the outcome of disease for each patient were obtained. The patients were divided into cardiac and non-cardiac groups based on echocardiographic results. RESULTS: In total, 104 patients with KD (66 boys and 38 girls) were enrolled in this study. The male to female ratio was 1.7:1. The mean ± SD age of the patients was 33.6 ± 24.2 months. Most (87.2%) cases were from urban areas. The disease occurred more frequently during winter and spring. Furthermore, 61.5% of the children had the criteria of classic KD, and 38.5% were labeled as incomplete KD. The mean ± SD of the duration of hospital stay was 6.9 ± 2.4 days. The mean time between illness and admission to the hospital was 6.47 ± 2.6 days. The most common sign was fever, followed by conjunctivitis and oral changes. In total, 20% of the patients had cardiac abnormalities. There was no significant statistical difference between the cardiac and non-cardiac groups according to age, sex, clinical manifestations, laboratory findings, and cessation of fever. The duration of hospital stay and the time between onset of illness and diagnosis were longer in the cardiac group. All patients received intravenous immunoglobulin and aspirin. Only one patient continued to have cardiac abnormalities after 6 months of follow-up. CONCLUSIONS: Kawasaki disease is not rare in southwest of Iran. The age, gender distribution and clinical findings are similar to that of other reports. Patients with cardiac abnormalities had delayed treatment and prolonged hospital stays.